A family of lanthanide compounds based on nitronyl nitroxide radicals: synthesis, structure, magnetic and fluorescence properties. Issue 61 (9th August 2017) - Lv, Xue-Hui; Yang, Shuai-Liang; Li, Yuan-Xia; Zhang, Chen-Xi; Wang, Qing-Lun
Abstract : A series of lanthanide nitronyl nitroxide radical compounds have been synthesized and characterized structurally and magnetically. Abstract : A series of lanthanide nitronyl nitroxide radical compounds, [Ln(hfac)3 (NITPh- p -N(CH3 )2 )2 ]· x C7 H16 (Ln = La (1 ), Eu (2 ), Gd (3 ), Tb (4 ), Dy (5 ), Er (6 ), hfac = hexafluoroacetylacetonate; NITPh- p -N(CH3 )2 = 4′-dimethylamino-phenyl-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide, x = 2/3 for complexes1, 2, 3 and6, and 0 for4 and5 ), have been synthesized and structurally characterized. X-Ray crystallographic analyses show that the structures of the six compounds are similar and all consist of isolated molecules, in which central Ln(iii ) ions are coordinated to six oxygen atoms from three hexafluoroacetylacetonate ligands and two oxygen atoms from nitronyl nitroxide radicals. Variable-temperature magnetic susceptibility studies reveal ferromagnetic interactions between the Gd(iii ) ion and nitronyl nitroxide radical in complex3 . Ac magnetic susceptibility measurements of complexes4 and5 exhibit frequency-dependent out-of-phase signals, indicating single-molecule magnet (SMM) behavior.